Rudymentarne zasady życia społecznego w ujęciu Edmunda Wnuka-Lipińskiego - Dobrogowska, Monika (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
The article explains and analyses those principles of social life which Edmund Wnuk-Lipiński defines as of topical social significance. It is revealed that the sociologist attaches great importance to the principle of common good. It is also shown that in his works, Wnuk-Lipiński takes into account the principle of subsidiarity and approaches it from the perspective of state and statehood. The sociologist attributes an important role to the principle of solidarity in democratic systems. In his opinion, solidarity led the Polish society of the 1980s to unite in active resistance to the Communist regime. As argued by E. Wnuk-Lipiński, since 1989 we have been witnessing an axiological and sociological atomisation of the attitudes displayed by Poles, which has led to increased social stratification. In this context, the sociologist discusses the principle of social trust to argue that its level is extremely low in contemporary Polish society. E. Wnuk-Lipiński puts major responsibility for this fact on the ruling elites and their actions.